USING EDUCATIONAL DIGITAL TOOLBOX IN E-LEARNING tO BOOST STUDENTS’ READING MOTIVATION IN COVID-19 PANDEMIC - Anastasia Dewi Anggraeni; Helda Jolanda Pentury (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aimed at investigating  the use of educational digital toolbox in e-learning to motivate college students’ reading motivation, such as recognizing ideas, comprehending texts using graphics, images, and charts, audio, audio-visual and video to personal experience, opinion or evaluation. The study attempted the qualitative method. The instrument used was a questionnaire which were prepared for the purpose and which was administered to 84 students at Indraprasta university, majoring in English education department in South Jakarta, during March and April 2020. The result of this study shows most of students boost their reading motivation by using educational digital toolbox in e-learning process. Give the new perspective that language students can be motivated to use long distance learning more active and more interactive, as well as enrich their learning experiences. Moreover, using appropriate pedagogical implementations such as effective digital toolboxes, interesting reading topics and students’feedback can boost students’ reading motivation with the changing learning trend.